The teaching profession in the face of Covid-19: an approach from the employment precariousness of the part-time teacher - Barbosa-Bonola, Viviana; Ávila-Carreto, Armando (IE Revista de Investigación Educativa de la REDIECH, 2022)
The thoughts shared in this essay aim to highlight job insecurity in Higher Education Institutions (HEI) during COVID-19, portraying specifically the work of a teacher. In order to understand how the logic of job insecurity leads to the practice of undermining and minimizing the education professional, it is proposed to reflect on the effects that have occurred since the beginning of the pandemic. Finally, some critical proposals are highlighted to address the labor vulnerability of the teaching community in HEIs, based on the recognition of human, social, economic, and labor rights.